Benzodiazepine use disorder: A cross-sectional study at a tertiary care center in Lebanon. Issue 38 (23rd September 2022) - El Zahran, Tharwat; Kanaan, Elie; Kobeissi, Lynn; Bouassi, Joseph; Sarieddine, Aseel; Carpenter, Joseph; Kazzi, Ziad; Hitti, Eveline
Abstract : Benzodiazepines are medications used for the treatment of multiple conditions including anxiety disorders, insomnia, agitation, and seizures. They are the most prescribed psychiatric medications and the third most misused drugs among adults and adolescents in the US. This study aims to assess the patient utilization patterns and benzodiazepine use disorder among Lebanese patients. A cross-sectional study was performed on Lebanese patients presenting to the Emergency Department of the American University of Beirut Medical Center (AUBMC), between November 11th, 2019, and May 30th, 2020. Institutional review board approved the study, and an informed consent was obtained from patients. A total of 244 patients were included in the final analysis. A total of 154 (63.1%) patients were found to have benzodiazepine use disorder as per the DSM-V criteria with the majority (64%) being females and young adults aged 18 to 40 years. The most common medication was alprazolam, and anxiety was the most common reason for benzodiazepine use. The majority (88%) of patients obtained their medications using a physician's prescription. More than half of users were not satisfied with the physician's instructions and lacked knowledge about side effects and abuse potential. The high rate of benzodiazepine misuse among our young adults highlights an important public health concern that requires interventions and policy implementation.